EP-44 Improving Patient Education About Pre-Diabetes. (9th August 2022) - Carey, Charles; Natarajan, Shanthi
Abstract: Pre-diabetes is a common condition and although its development is heavily linked to lifestyle factors, many patients are unaware of interventions that can improve their condition. One-to-one consultations between patients and GPs focused on reducing carbohydrate consumption have been shown to be effective at improving pre-diabetes. This QIP aimed to improve patients' understanding of pre-diabetes and reduce their carbohydrate intake. Patients were included if they had 2 HbA1c measurements between 42 – 48mmol/mol and the ability to make dietary changes independently. A questionnaire based on the UK Diabetes and Diet Questionnaire was constructed and used to ask patients about their concern about pre-diabetes, knowledge of foods that contribute to the condition and the frequency at which they consumed various carbohydrates. Advice about reducing carbohydrate intake was given verbally and patients were provided with a diet sheet produced by Unwin et al. Patients were called again after 7–14 days to assess dietary changes and the impact of the advice. 31 patients responded to the initial telephone call of which 58.1% were concerned about pre-diabetes and 38.7% mentioned foods high in carbohydrate as a cause of pre-diabetes. 90.3% of patients consumed food high in carbohydrate on 4 or more days per week. 22 patients responded to the follow up telephone call of which 63.6% reported a reduction in carbohydrate intake, 95.5% knew more about pre-diabetes and 90.9% found the dietary advice helpful. These results suggest that pre-diabetic patients should be given verbal and written information about lowering carbohydrate intake at GP consultations.